Measuring Program Impacts on Earnings and Employment: Do Unemployment Insurance Wage Reports from Employers Agree with Surveys of Individuals? - Kornfeld, Robert; Bloom, Howard S. (Journal of Labor Economics, 1999)
This article attempts to determine whether wage records reported by employers to state unemployment insurance (UI) agencies provide a valid alternative to more costly retrospective sample surveys of individuals as the basis for measuring the impacts of employment and training programs for low‐income persons. We analyze UI data and survey data for a sample of low‐income adults and youths from 12 sites in the National Job Training Partnership Act (JTPA) study. Our comparison indicates that impact estimates based on UI data and survey data were usually comparable. However, average surveyreported earnings were higher than average UI‐reported earnings.